Analysis of the Indonesian Women's National Futsal Team Goalkeeper's Attacking Decision-Making During the 2026 ASEAN Women's Futsal Championship - Arina Dya (CV Abid Abadi Jaya, 2026)
The evolution of modern futsal has transformed the goalkeeper's role from merely defending the goal into becoming a key player in initiating attacking plays. Decision-making ability has become one of the primary factors influencing ball distribution effectiveness and offensive transition success. This study aimed to analyze the attacking decision-making of the Indonesian Women's National Futsal Team goalkeeper during the 2026 ASEAN Women's Futsal Championship. A quantitative descriptive approach was employed using document analysis through systematic observation of official match videos. The sample consisted of four matches played from the group stage to the semifinal against Thailand, Malaysia, Australia, and Vietnam. Data were analyzed using descriptive statistics, including frequencies and percentages. The results revealed that the effectiveness of ball distribution reached 74%, while goalkeeper playing achieved an effectiveness rate of 80%. The most dominant decision-making action was short ball distribution to teammates, performed 100 times with a 99% success rate, indicating a tactical preference for ball possession and build-up play. In contrast, long throws and volley kicks showed relatively low success rates. Regarding goalkeeper playing, the goalkeeper's involvement in kick-in and play-on situations achieved a 100% success rate, whereas long-range shooting recorded only 38% effectiveness. This study concludes that the Indonesian Women's National Futsal Team goalkeeper has successfully adopted the role of a modern goalkeeper in supporting attacking transitions. However, greater variation in attacking decision-making is still required to improve tactical effectiveness and overall team performance at the international level